Selection of 1-mm venting or 2.5-mm screw access holes on implant crowns based on cement extrusion and retention capacity - Huangjun Zhou; Sixian Ye; Min Liu; Hao Feng; Cai Wen (BMC, 2022)
Abstract Background This in vitro study aimed to provide evidence regarding the selection of hole diameters of implant crowns to reduce excess cement extrusion at the abutment margin, and to examine the maintenance of their retention capacity in anterior and posterior cement-retained implant crowns. Methods Six groups of implant crowns were prepared according to the position of the teeth and the size of their holes as follows: anterior crown without hole (ANH), anterior crown with 1-mm mini venting hole (AMH), anterior crown with 2.5-mm regular screw access hole (ARH), posterior crown without hole (PNH), posterior crown with 1-mm mini venting hole (PMH), and posterior crown with 2.5-mm regular screw access hole (PRH). Temporary cement was used to bond the crowns to the abutments. The mean amount of excess cement extrusion among the different groups at the abutment margin was calculated. Retentive strength under different hole designs was measured as the dislocation force of the crown using a universal testing machine. One-way ANOVA and Welch's t-test were used to analyze the results. Results The average amounts of extruded excess cement were 18.96 ± 0.64, 1.78 ± 0.41, and 1.30 ± 0.41 mg in the ANH, AMH, and ARH groups, respectively, and 14.87 ± 0.36, 1.51 ± 0.40, and 0.82 ± 0.22 mg in the PNH, PMH, and PRH groups, respectively. The hole opening in the crowns could significantly reduce residual cement regardless of its size (p < 0.001). The mean retentive strengths were 54.16 ± 6.00, 47.63 ± 13.54, and 31.99 ± 7.75 N in the ANH, AMH, and ARH groups, respectively, and 57.84 ± 10.19, 53.22 ± 6.98, and 39.48 ± 5.12 N in the PNH, PMH, and PRH groups, respectively. The retention capacity of the implant crown deteriorated rapidly as the holes on the crown surface enlarged. Conclusions The presence of a hole on the implant crown reduced the amount of excess cement. The retention ability of the implant crowns deteriorated as the size of the hole increased. Considering the esthetic effect of the crown and the possible influence on crown retention, an implant crown with a 1-mm mini venting hole is a better clinical choice than the one with a 2.5-mm regular screw access hole.